Swipe, watch, buy: the hidden power of enjoyment, urgency, and influencers in live shopping - Ilyas, Gunawan Bata; Ilyas, Muh. Fadhel G Bata; Ginting, Yanti Mayasari; Tai, Quach Minh; Irfan, Andi (BISMA (Bisnis dan Manajemen), 2025)
This study investigates the key psychological and experiential factors influencing purchase decisions in live shopping environments, focusing on the Indonesian digital marketplace. This study examines how perceived enjoyment, promotional urgency, and influencer marketing affect purchase decisions, both directly and indirectly through consumer trust. It further explores the moderating role of platform experience. Using a quantitative approach with 265 valid responses analysed via Partial Least Squares Structural Equation Modelling (PLS-SEM), the results reveal that all three stimuli significantly influence consumer trust and purchase decisions. Trust is shown to mediate these effects, while platform experience strengthens the impact of the live shopping elements on purchase behaviour. The findings contribute to the growing literature on social commerce and offer practical insights for marketers and platforms seeking to enhance consumer engagement and conversion in live shopping settings. It provides empirical evidence on how perceived enjoyment, urgency-driven promotions, and influencer credibility shape real-time purchase decisions. This study is limited to Indonesia, affecting its broader applicability. Its cross-sectional nature and self-reported data may introduce bias. Future research should explore regional differences, behavioural analytics, and longitudinal studies on evolving consumer behaviours in live shopping.